2022
DOI: 10.1007/s11136-022-03247-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential associations of emotional and physical domains of the MacNew Heart with changes in 6-min walking test

Abstract: Aims Cardiac rehabilitation (CR), a key component of secondary prevention in cardiac patients, contributes fundamentally to improved cardiovascular health outcomes. Health-related quality of life (HRQOL) represents a widely employed outcome measure in CR, yet, its predictive properties on exercise capacity change during CR are poorly understood. Aim of this study was to examine the association between baseline HRQOL and its subdomains on improvement of exercise capacity during CR. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Moreover, a prospective and an observational study revealed the strong impact of age, gender, residence, marital status, monthly income and clinical factors like comorbidities and number of hospitalizations on HRQOL and functional status of the patient. 15,20 An observational study conducted by Wu JR 13 and a cross-sectional study conducted by Jellestad L et al 21 and Wang G 15 concluded that the functional capacity is associated with the quality of life of patients who had undergone cardiac interventions. This is same as the results of present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a prospective and an observational study revealed the strong impact of age, gender, residence, marital status, monthly income and clinical factors like comorbidities and number of hospitalizations on HRQOL and functional status of the patient. 15,20 An observational study conducted by Wu JR 13 and a cross-sectional study conducted by Jellestad L et al 21 and Wang G 15 concluded that the functional capacity is associated with the quality of life of patients who had undergone cardiac interventions. This is same as the results of present study.…”
Section: Discussionmentioning
confidence: 99%